Shell Injuries in Two Intertidal Gastropods Littorina scabra (Linnaeus, 1758) and Thais bufo (Lamarck, 1845) From Tranquebar, Southeast Coast of India - Kaila Kesavan; Velayudham Ravi; Santhanam Rajagopal (Marine Science Department Diponegoro University, 2009)
Littorina scabra and Thais bufo were collected from the rocky shore of Tranquebar and the shell injury due to predation or wave action was estimated in both male and female snails. In both the cases, the results show that the shell injury is not depending on shell size but mainly on their exposure to continuous wave action. The physical damage caused to them due to the rolling of small rocks, boulders and the risk ofpredation was mainly from crabs and birds. 'n the present study a survey has been made to estimate the percentage ofsheil injury in male and female snails and different size groups of the above two different species. Obviously there is a relationship between crabs, stones md shell damage. In L scabra the shell damage in male and female was 47.18% and 41.1% and the size group m 16.10 mm to 18.10 mm is dominant with 28.44% of shell injury. Whereas in T. bufo it was 50.81% in male and 44.44% in female and the size group of 40.01 mm to 48.10 mm is dominant with 21.22% ofsheil injury respectively. The male and female of both the species for the length and width ofsheil damage were positively correlated. Anova for within the species in shell damage in L. scabra didn't show variation but forT. bufo it showed variation. Anova for between the species showed significant variation. Among these the female in L. scabra and male in T. bufo showed a maximum injury .This may be able to asses the threat to organisms and shows the level ofpredation and the damage caused by environmental factors. Key words : Tranquebar, gastropods, predation, shell injury, rocky shore